Thermo-mechanical properties of cubic titanium nitride. Issue 5 (24th March 2018) - Mohammadpour, Ehsan; Altarawneh, Mohammednoor; Al-Nu'airat, Jomana; Jiang, Zhong-Tao; Mondinos, Nicholas; Dlugogorski, Bogdan Z.
Abstract: The equilibrium structure, elastic constants C ij and thermodynamic functions of cubic titanium nitride (TiN) were calculated within the temperature range of 0–3100 K and under a pressure range 0–60 GPa. Properties were computed using the generalised gradient approximations (GGA) exchange-correlation functional. Calculated mechanical properties (Elastic constants, Young's modulus and shear modulus) and phonon spectra of TiN obtained via robust DFT-QHA algorithm, were generally in a good agreement with available experimental and theoretical analogous values. In particular, a well-examined quasi-harmonic approximation method implemented in the Gibbs2 code is utilised herein to provide accurate estimation of thermal expansion coefficients, entropies, heat capacity values (at different combinations of temperature/volume/pressure) and Debye's temperature. Parameters calculated herein shall be useful to elucidate the superior performance of TiN at harsh operational conditions encompassing elevated temperatures and pressures pertinent to cutting machineries and surface coatings.